New York Paper - Effect of Cold-working and Rest on Resistance of Steel to Fatigue under Reversed Stress (with Discussion) - H. F. Moore; W. J. Putnam (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
THIS paper gives a preliminary summary of results of tests on the resistance to fatigue under reversed stresses of steel subjected to cold-working and of tests to determine the effect of rest on the endurance of steel under reversed stresses. The tests of cold-worked steel were undertaken as part of an investigation by the National Research Council Committee on Fatigue Phenomena of Metals and were made by Mr. Moore; the tests to determine the effect of rest are part of an investigation now being made by Mr. Putnam. Both series of tests were made in the Materials Testing Laboratory of the University of Illinois. The preliminary results of these tests are reported now because it is believed that test data on fatigue strength should be available at the earliest possible moment; however, it should be clearly kept in mind that this paper gives preliminary results and is intended to encourage discussion rather than to give final conclusions. Before giving the data of the tests, the writers will explain the term "fatigue strength" as used in this paper and will discuss briefly the method used in interpreting the test data of repeated-stress tests. " The term fatigue strength, as applied to a material, may be defined as that maximum fiber stress that will cause fracture of the material after the repetition of any given number of cycles of stress, each cycle involving the variation of stress from a minimum to the above maximum. The fatigue strength, then, varies with the number, of repetitions occurr,ing in the lifetime of a structural or machine member and with the range of stress for each cycle of stress. The fatigue strength will be lower for a member in which the stress is completely reversed than for one in which the stress varies from zero to a maximum. In interpreting test data from fatigue tests under reversed stress, the stresses and corresponding numbers of repetitions required for failure are plotted on logarithmic cross-section paper. In 1910, Professor